2021
DOI: 10.3389/fphar.2021.587003
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone Treatment in Brain Death-Induced Lung Inflammation–A Dose Comparative Study in Rats

Abstract: Background: The process of brain death (BD) leads to a pro-inflammatory state of the donor lung, which deteriorates its quality. In an attempt to preserve lung quality, methylprednisolone is widely recommended in donor lung management. However, clinical treatment doses vary and the dose-effect relation of methylprednisolone on BD-induced lung inflammation remains unknown. The aim of this study was to investigate the effect of three different doses methylprednisolone on the BD-induced inflammatory response.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…As mentioned previously, the process of brain death leads to a pro-inflammatory state in the donor lung, which deteriorates its quality. To preserve lung quality, studies use different forms of treatment to reduce this inflammation, like we found in studies involving the use of methylprednisolone, and carbon monoxide inhalation 29 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, the process of brain death leads to a pro-inflammatory state in the donor lung, which deteriorates its quality. To preserve lung quality, studies use different forms of treatment to reduce this inflammation, like we found in studies involving the use of methylprednisolone, and carbon monoxide inhalation 29 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Pilla et al also showed in their study that 30 mg/kg of methylprednisolone, 5 and 60 min after induction of BD, intravenously also reduced the levels of TNF-α in lung tissue. In the study by Zhou et al they demonstrated that carbon monoxide inhalation was able to reduce lung injury (anti-inflammatory action, due to the reduction of IL-6 and TNF- α and antiapoptotic agents) in rats subjected to brain death 29 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage chemotaxis was attenuated with all doses of methylprednisolone, while neutrophil chemotaxis was more evident with intermediate and high doses of methylprednisolone. Considering dose-related side effects of methylprednisolone, this study suggested the intermediate dose of methylprednisolone reduced brain death-induced inflammatory responses in donors’ lungs[ 63 ]. These findings need human studies before extrapolation to routine clinical use.…”
Section: Transplant Donorsmentioning
confidence: 99%
“…Thus, more studies are needed to understand how deficiency in the leptin signaling may switch the GC action from protection to aggravation in liver IRI and thus affect GC action in SOT of liver and other organs in humans. [63] . These findings need human studies before extrapolation to routine clinical use.…”
Section: Transplant Donorsmentioning
confidence: 99%